Africa in the 1980s : a continent in crisis - Legum, Colin (New York : McGraw-Hill, 1979)
The studies in this volume explore the political and social problems and other constraints on development in Africa.
Includes bibliographical: p. 213-218 and index.
oif 10/04/2019
Loans
Keywords: Politics and government; Economic history; Economic conditions; Africa